Parasitic Nematode-Induced Modulation of Body Weight and Associated Metabolic Dysfunction in Mouse Models of Obesity - Yang, Zhonghan (American Society for Microbiology, 2013)
Obesity is associated with a chronic low-grade inflammation characterized by increased levels of proinflammatory cytokines that are implicated in disrupted metabolic homeostasis. Parasitic nematode infection induces a polarized Th2 cytokine response and has been explored to treat autoimmune diseases. We investigated the effects of nematode infection against obesity and the associated metabolic dysfunction. Infection of RIP2-Opa1KO mice or C57BL/6 mice fed a high-fat diet (HFD) with Nippostrongylus brasiliensis decreased weight gain and was associated with improved glucose metabolism. Infection of obese mice fed the HFD reduced body weight and adipose tissue mass, ameliorated hepatic steatosis associated with a decreased expression of key lipogenic enzymes/mediators, and improved glucose metabolism, accompanied by changes in the profile of metabolic hormones. The infection resulted in a phenotypic change in adipose tissue macrophages that was characterized by upregulation of alternative activation markers. Interleukin-13 (IL-13) activation of the STAT6 signaling pathway was required for the infection-induced attenuation of steatosis but not for improved glucose metabolism, whereas weight loss was attributed to both IL-13/STAT6-dependent and -independent mechanisms. Parasitic nematode infection has both preventive and therapeutic effects against the development of obesity and associated features of metabolic dysfunction in mice.